Assessing samarium resource efficiency in China: A dynamic material flow analysis. (June 2022) - Ge, Zewen; Geng, Yong; Wei, Wendong; Zhong, Chen
Abstract: Samarium is one rare earth element that plays a vital role in the emerging high-tech sectors. However, few studies have been conducted to investigate this element. This study aims to investigate samarium flows and stocks in China for the period of 2011–2020 through dynamic material flow analysis. Also, a linear programming method is employed to predict future samarium demand and supply until 2035. The results show that the annual demand for samarium significantly increased from 162 tons in 2011 to 726 tons in 2020, while its supply remained stable with an annual amount of 600 tons. Due to this supply-demand imbalance, the total samarium surplus decreased to 1140 tons in 2020. Without any intervention policies, samarium resource will be depleted before 2025. From a trade perspective, China has exported more samarium resources to other countries due to its abundant reserves, which may influence its domestic supply. Finally, several policy recommendations are proposed to improve the overall samarium resource efficiency, including economic instruments, technological support, and the implementation of circular economy. Highlights: This study investigates samarium flows and stocks in China by using dynamic material flow analysis. Demand for samarium increased from 162 tons in 2011 to 726 tons in 2020 in China. Samarium's supply remained stable with an annual amount of 600 tons. Samarium surplus decreased to 1140 tons in 2019 due to imbalanced supply-demand. Policy recommendations were proposed to improve samarium resource efficiency.